Pengaruh Auditor Switching, Kompleksitas Operasi Perusahaan, Dan Audit Complexity Terhadap Audit Report Lag (Studi Empiris Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar I Bursa Efek Indonesia Periode 2019-2023) - Naungan Sihombing; Nofryanti (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to analyze the influence of auditor switching, company operational complexity, and audit complexity on audit report lag in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. This study uses a quantitative method with a multiple linear regression approach. The research sample was selected using purposive sampling techniques, resulting in 47 companies that met the criteria during the observation period, with a total of 235 observational data points. The data used were secondary data in the form of annual financial statements published by the companies. The research results show that partially, (1) Auditor Switching does not affect Audit Report Lag. (2) Company Operational Complexity has a positive and significant effect on Audit Report Lag. (3) Audit Complexity does not significantly affect Audit Report Lag. These findings indicate that the more complex a company's operations, the longer it takes for the auditor to complete the financial statement audit process.